THE ORIGIN, EVOLUTION AND CHANGING PERSPECTIVES OF WIDOWHOOD IN THE BAMENDA GRASSFIELDS OF CAMEROON SINCE THE PRECOLONIAL PERIOD - Ankiambom, Linda (PEOPLE: International Journal of Social Sciences, 2017)
This paper examined the practice of widowhood in the Bamenda Grassfields of Cameroon since the pre-colonial period. Every society struggling to deal with women who lost their husbands ended up with some norms for widows during widowhood. This was done through the developing of rules which were very often reactions to past and common experiences. The rules often sought to deal with the people’s fears, loves, hopes and aspirations. However, widowhood eventually lost its original reasons and increasingly became a problem in most if not all African societies. The objective of this work has been to trace the original reasons for the practice of widowhood rites and how they evolved and experienced change in some selected communities of the Bamenda Grassfields. It is also to explain the culture of widowhood in the Bamenda Grassfields so that such an understanding could guide researchers in the search for solutions to the widowhood practices. Following a historical research guided by a questionnaire, both primary and secondary sources were consulted. Oral interviews were conducted with resourceful individuals and a selected group of widows in the study locale. The analysis of the data collected led to the conclusion that the practice of widowhood in this area evolved with different historical moments and circumstances and has come to toe the line with feminism and contemporary laws.